Improving Shear Strength Of Expansive Soil Through Asphalt Emulsion And Local Pozzolanic Additives - Oktofani, Khansa Nuansa; Syahril, Syahril; Indra Noer Hamdhan; Naess, Victor Firstkiel Feber (Journal of Green Science and Technology, 2025)
Expansive clayshale soils pose a significant geotechnical challenge due to their high swell-shrink potential and low shear strength, necessitating urgent development of effective and sustainable stabilization methods. This study explores the stabilization of such problematic soils using a combination of emulsified asphalt (AE) and Bledug Kuwu mud (LBK), a natural pozzolanic byproduct derived from a unique geological phenomenon in Central Java, Indonesia. A total of 51 cylindrical specimens were prepared with a fixed 8% AE content and varying LBK contents (6%, 10%, 14%, and 18%) by dry weight of soil. The mechanical properties were evaluated using Unconsolidated Undrained (UU) triaxial tests, while Scanning Electron Microscopy (SEM) was employed to examine microstructural evolution. The results highlight a marked improvement in shear strength parameters cohesion (c) and internal friction angle (φ)—in tandem with increased LBK content and curing duration. The optimal mixture (18% LBK, 8% AE, and 14 days of curing) showed a significant rise in c from 79.46 kPa to 150.88 kPa and φ from 14.3° to 24.0°, indicating a synergistic interaction between the asphalt binder and pozzolanic compounds. SEM analysis confirmed the formation of a denser and more cohesive matrix, attributed to both the physical encapsulation effect of AE and the pozzolanic reaction products, particularly calcium silicate hydrate (C–S–H) and calcium aluminate hydrate (C–A–H), which enhanced interparticle bonding. These findings underscore the effectiveness and urgency of adopting AE–LBK stabilization as a cost-efficient and environmentally friendly alternative for improving expansive soils. The study provides a foundational basis for field-scale implementation and long-term performance assessment in infrastructure development on marginal ground.